Analisis Strategi Promosi Media di Kantor KPU Parepare - Azis, Asriani; Sulfiyati, Sulfiyati; Putrawan, Putrawan; August, Giant; Dinsar, Arfandi (Jurnal Ilmiah Multidisiplin Amsir, 2023)
This research uses a qualitative approach to analyse the media promotion strategy at the Parepare Regional Election Commission (KPU). The aim is to understand the factors influencing media promotion strategies' design, implementation, and effectiveness in the face of media dynamics and public participation in elections. The research methods involve in-depth interviews, participatory observation, and content analysis of promotional materials. The analysis aims to identify successes and challenges and provide recommendations for improvement. Practical implications include enhancing KPU Parepare's understanding of utilizing media promotion to increase community engagement and trust in the electoral process. The research conclusions are expected to serve as a basis for strategically planning more effective and locally responsive campaign media promotion.